In Rheumatoid Arthritis Patients, HLA-DRB1*04:01 and Rheumatoid Nodules Are Associated With ACPA to a Particular Fibrin Epitope - Larid, Guillaume; Pancarte, Mikael; Offer, Géraldine; Clavel, Cyril; Martin, Marielle; Pradel, Vincent; Auger, Isabelle; Lafforgue, Pierre; Roudier, Jean; Serre, Guy; Balandraud, Nathalie (Frontiers in Immunology, 2021)
Objectives: Rheumatoid arthritis (RA) is associated with HLA-DRB1 genes encoding the shared epitope (SE), a 5-amino acid motive. RA is usually preceded by the emergence of anti-citrullinated protein/peptide antibodies (ACPAs). Citrulline is a neutral amino acid resulting from post-translational modification of arginine involved in peptidic bounds (arginyl residue) by PeptidylArginine Deiminases (PADs). ACPAs recognize epitopes from citrullinated human fibrin(ogen) (hFib) and can be specifically detected by the AhFibA assay. Five citrullinated peptides derived from hFib together represent almost all of the epitopes recognized by patients with ACPA-positive RA, namely : α36–50cit, α171–185cit, α501–515cit, α621–635cit, and β60–74cit. The use of antibody fine specificities as markers of clinical phenotypes has become a major challenge. Our objective was to study whether RA clinical characteristics and HLA-DRB1 genetic background were associated with a specific reactivity against the epitopes borne by the five peptides. Methods: 184 ACPA-positive RA patients fulfilling the 2010 ACR/EULAR criteria were studied. Patient characteristics including HLA-DRB1 genotype, were collected from their medical files. Anti-CCP2 antibodies, AhFibA, and antibodies against the five citrullinated hFib (hFib-cit) peptides were analyzed by ELISA. Results: Anti-α505-515cit antibodies were associated with HLA-DRB1*04:01 (OR = 5.52 [2.00 – 13.64]; p = 0.0003). High level anti-α505-515cit antibodies were associated with rheumatoid nodules (OR = 2.71 [1.00 – 7.16], p= 0.044). Conclusion: Immune complexes containing anti-α501-515cit antibodies and rheumatoid factors might be involved in the development of rheumatoid nodules on the HLA-DRB1*04:01 background. Apheresis of these epitope-specific antibodies might be a new therapeutic opportunity for patients with rheumatoid nodules